2022
DOI: 10.3390/molecules27041235
|View full text |Cite
|
Sign up to set email alerts
|

Production and Digestibility Studies of β-Galactosyl Xylitol Derivatives Using Heterogeneous Catalysts of LacA β-Galactosidase from Lactobacillus Plantarum WCFS1

Abstract: The synthesis of β-galactosyl xylitol derivatives using immobilized LacA β-galactosidase from Lactobacillus plantarum WCFS1 is presented. These compounds have the potential to replace traditional sugars by their properties as sweetener and taking the advantages of a low digestibility. The enzyme was immobilized on different supports, obtaining immobilized preparations with different activity and stability. The immobilization on agarose-IDA-Zn-CHO in the presence of galactose allowed for the conserving of 78% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In another study, the one-step glycosylation of flavonoids was investigated [40]. One strain of Isaria fumosorosea KCH J2 and two strains of I. farinosa (J1.4 and J1.6) were used as biocatalysts for the glycosylation of 3-hydroxyflavone, 3-methoxyflavone, quercetin (3,3 ,4 ,5,7-pentahydroxyflavone), and baicalein (5,6,7-trihydroxyflavone) [41]. For all the substrates that were used in this study, 4-O-methylglucopyranosides were obtained and the authors suggested that the attachment of 4-O-methylglucopyranose occurs in one step.…”
Section: Microbial Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the one-step glycosylation of flavonoids was investigated [40]. One strain of Isaria fumosorosea KCH J2 and two strains of I. farinosa (J1.4 and J1.6) were used as biocatalysts for the glycosylation of 3-hydroxyflavone, 3-methoxyflavone, quercetin (3,3 ,4 ,5,7-pentahydroxyflavone), and baicalein (5,6,7-trihydroxyflavone) [41]. For all the substrates that were used in this study, 4-O-methylglucopyranosides were obtained and the authors suggested that the attachment of 4-O-methylglucopyranose occurs in one step.…”
Section: Microbial Glycosylationmentioning
confidence: 99%
“…The synthesis was performed using lactose as a donor and good yields for all the interesting compounds were obtained. The in vitro intestinal digestibility of the main β-galactosyl xylitol derivatives was lower than that of lactose, being around 6 and 15% for the galacto-xylitol derivatives compared to 55% for lactose after 120 min of digestion [41]. Another interesting example has been described in the stereoselective glycosylation of epothilones.…”
Section: Enzymatic Glycosylation Of Other Alcoholsmentioning
confidence: 99%